The joy of conversation evangelization, wisdom, and dialogue - Hayes, Katherine Murphey 1947- (2016)
Although produced at a Lutheran seminary, Word & World has always sought to widen its perspectives by incorporating the ideas of those from other religious traditions, partially through its Advisory Council. An active member of this group is Old Testament scholar Katherine Hayes, who teaches at the Seminary of the Immaculate Conception, Huntington, New York.
Keywords: Bible. Job -- Theology; Bible. Proverbs -- Theology; Burtness, James H, 1928-2006; Catholic Church, Pope (2013- : Francis) -- Evangelii gaudium; Catholic Church -- Relations; Dialogue (Theology); Evangelistic work -- Theory; Gaiser, Frederick J; Vatican Council (2nd : 1962-1965) -- Church in the modern world; Vatican Council (2nd : 1962-1965) -- Revelation; Wisdom -- Biblical teaching; Word & World (Periodical)